Fiscal Dimensions of Trade Policy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper assembles findings on the use of trade taxes, examines the main contributing factors, and reviews the fiscal aspects of trade policy as they relate to both efficiency and macroeconomic stabilization. It demonstrates why trade taxes would generally not be part of an optimal tax package, and describes the conditions under which they could be used and what their structure would be. The paper also reviews the channels of the effects of trade taxes under fixed and flexible exchange rates, and concludes that the distortions and welfare loss that they create put them at a disadvantage vis-a-vis other fiscal and exchange rate policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet